Analysis of Htra Gene from Zebrafish (Danio Rerio) - M. Murwantoko; Chio Oka; Masashi Kawaichi (Indonesian Journal of Biotechnology, 2005)
HtrA which is characterized by the combination of a trypsin-like catalytic domain with at least one C-terminal PDZ domain is a highly conserved family of serine proteases found in a wide range of organisms. However the identified HtrA family numbers varies among spesies, for example the number of mammalian, Eschericia coli, fruit fly-HtrA family are 4, 3 and 1 gene respectively. One gene is predicted exist in zebrafish. Since no complete information available on zebrafish HtrA, in this paper zebrafish HtrA (zHtrA) gene was analyzed. The zHtrA is belonged to HtrA1 member and predicted encodes 478 amino acids with a signal peptide, a IGF binding domain, a Kazal-type inhibitor domain in the up stream of HtrA-bacterial homolog. At the amino acid sequence the zHtrA1 showed the 69%, 69%, 68%, 54% and 54% with the rat HtrA1, mouse HtrA1, human HtrA1, human HtrA3 and mouse HtrA4 respectively. The zHtrA1 is firstly expressed at 60 hpf and mainly in the vertebral rudiments in the tail region.